Pernikahan Lintas Agama dalam Perspektif Hadits - Sawaun Sawaun (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2016)
This article examines, historically, model of interfaith marriages from hadith perspective. There are two models of interfaith marriages, i.e. a marriage between Muslim, men or women, with musyrik (polytheists) community and ahl al-kitâb. Thisstudy concluded that a marriage between a Muslim with polytheists community has no foundation in tradition (hadith), and never practiced by the early generations of Islam. Meanwhile, male Muslim marriage with ahl al-kitâb has strong historical foundationin the early generations of Muslims. While marriage between Muslim women with ahlal-kitâb wasn’t discovered a historical evidence of it permission, either the Prophetwords or the practice of Companions.